Sensitivity to asbestos is increased in patients with mesothelioma and pathogenic germline variants in BAP1 or other DNA repair genes. Issue 11 (19th October 2018) - Betti, Marta; Aspesi, Anna; Ferrante, Daniela; Sculco, Marika; Righi, Luisella; Mirabelli, Dario; Napoli, Francesca; Rondón‐Lagos, Milena; Casalone, Elisabetta; Vignolo Lutati, Francesca; Ogliara, Paola; Bironzo, Paolo; et al.
Abstract: Pathogenic germline variants in the BAP1 tumor suppressor gene can cause a cancer syndrome called BAP1 tumor predisposition syndrome ( BAP1 ‐TPDS), which is characterized by predisposition to mesothelioma, melanoma, renal cell carcinoma, basal cell carcinoma, and other tumors. Other genes that may predispose to mesothelioma are CDKN2A and DNA repair genes. Asbestos exposure has often been reported in patients with malignant pleural mesothelioma (MPM) and germline variants in BAP1, but this exposure has never been quantified. We aimed to search for germline variants in BAP1 among 25 new Italian probands with suspected BAP1 ‐TPDS, summarize the prevalence of these variants in 39 Italian patients with familial MPM and other tumors recruited over a 5‐year period, and compare cumulative asbestos exposure in 14 patients with MPM and pathogenic germline variants in BAP1, CDKN2A, or DNA repair genes with that of 67 patients without germline variants in 94 cancer‐predisposing genes. We report here a new pathogenic germline variant in BAP1 : c.783 + 2 T > C. The prevalence of pathogenic germline variants in BAP1 was 7.7% among patients with familial MPM (3/39). Patients with pathogenic germline variants in BAP1, CDKN2A, or DNA repair genes showed lower cumulative asbestos exposure than patients without germline variants in 94 cancer‐predisposing genes ( P = .00002). This suggests an interaction between genetic risk factors and asbestos in the development of mesothelioma.